(3eYGde GdOjfs - (3GdYGedj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, J (B966(3g` (B1559(3es ((3eMSf SYOjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdeJYGdj Yf eYGQL GdCagGe adG jMjW Hcfgg GdYGQahf, GdeJbOS ceGd PGJg Yf eTGHgI GdCfGe (B... (3aEf Chdi eG CfabJ aj JMUjdg cfhR GdCYeGds
(3BNQgG (B:s
(3BNQgG(B: (3hEf cGf eMJekdG EdG Cf GMJeGd GdJbjI Ydi eG gh GdeYdhe ef CMhGd GdCFeI Ydjge GdSdGe CbQH hCXgQ aj Pdc cGf aj GdJQLjM hcdGe GdTjN YfOj gh GdMb(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B3: 64s
(3GdPQjYI, L (B21: 130s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs